(untitled) (Research, Society and Development, 2021)
Objective: Evaluate the peripheral muscle strength of hospitalized individuals with respiratory disorders undergoing an early mobilization protocol. Methods: Sixteen hospitalized patients with pulmonary diseases were randomly randomized to the Early Mobilization (EM) group and the Early Mobilization group associated with the Cycle ergometer (EM+C). Cardiorespiratory parameters and peripheral muscle strength were evaluated before and after the intervention, through the Peg Board and Ring Test (6PBRT) and the Handgrip Strength (HGS) test. The data were expressed as (average and standard deviation) for parametric data and (median and interquartile range) for nonparametric data, using the GraphPad Prism 8.0 program, using the t-student test (paired and unpaired), Wilcoxon, one-way ANOVA and post test Tukey, Kruskal-Wallis and post test Dunn, with the significance level adopted for the statistical treatment of (p <0.05). Results: The 6PBRT revealed statistical difference when comparing pre and post intervention of the EM and EM+C groups, respectively (p=0.01) and (p=0.006). The HGS test revealed a statistically significant difference when comparing pre and post intervention of the EM and EM+C groups, respectively (p=0.03) and (p=0.008). Conclusion: It is concluded that early mobilization associated with the cycle ergometer may demonstrate a significant increase in peripheral muscle strength, confirmed by 6PBRT and HGS, which proved to be effective evaluation methods.